Correlation between cervical vertebral bone age and mandibular growth potential in a Javanese population: Korelasi antara cervical vertebral bone age dengan potensi pertumbuhan mandibula pada populasi suku Jawa - Marsellina Iduberga Mening Ibau; Annisa Putri; Basma Rosandi Prakosa; Raden Aditya Wisnu Wardhana (Makassar Dental Journal, 2026)
Assessment of mandibular growth potential is important in orthodontic treatment planning. Bone age, such as cervical vertebral bone (CVB) age, is consider-ed more accurate than chronological age in assessing skeletal maturation. This article discusses the correlation between CVB and mandibular growth poten-tial (MGP) in the Javanese population, through a correlative analytical study with a cross-sectional design, using 20 digital lateral cephalometric radiographs of Javanese patients aged 8-20 years. CVB measurements were performed using the Mito method, and MGP was calculated using a regression formula. At the initial stage, the mean CVB was 10.21 years, and MGP was 10.75 mm. At the final stage, CVB increased to 16.33 years, and MGP decreased to -1.53 mm. Pearson's test showed a significant negative correlation between CVB and MGP, Sig = 0.000 (p<0.05). It was concluded that there is a correlation bet-ween CVB and MGP in the Javanese population.